The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009 Proceedings of the 55th IEEE Holm Conference on Electrical Contacts 2009
DOI: 10.1109/holm.2009.5284397
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Remaining Lifetime of Power Connections Using Infrared Thermography

Abstract: One of the measures used to prevent the occurrence of power connection failures is to estimate the anomalous behavior of an electrical connection in the early stages of contact operation when the first signs of critical stage become apparent. This paper investigates the possibility of applying the statistical prognostic methods for determining the residual life of power connections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
3
Order By: Relevance
“…Braunovic et al [12] discutiram a correlação entre a temperatura e a resistência de contato. Em [13] e [14], os autores propuseram alguns métodos para medir a resistência de contato.…”
Section: Estratégias De Manutenção Em Disjuntorunclassified
“…Braunovic et al [12] discutiram a correlação entre a temperatura e a resistência de contato. Em [13] e [14], os autores propuseram alguns métodos para medir a resistência de contato.…”
Section: Estratégias De Manutenção Em Disjuntorunclassified
“…While the SSE is large, Equation (8) is still an effective equation for determining the permissible interruption CIRCUIT BREAKER CONDITION-BASED MAINTENANCE 635 number at various interrupted currents. The optimal fitting curve is plotted in Figure 7 in which Equation (8) can offer the nearly same maintenance data provided by the manufacturer. The fact can also be verified by checking the second and third columns of Table IV.…”
Section: Case 2 -24 Kv 2000 a 25 Ka Vcb Studymentioning
confidence: 99%
“…Consequently, it can cause damage as the contacts melt. Braunovic et al discussed the correlation between the temperature and the resistance. In and , the authors proposed some methods for measuring the contact resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Braunovic et al have shown that the correlation between the temperature rise ∆T (t) and the resistance R(t) is around 0.9 [38]. Thus it is possible to study any of these parameters for monitoring the condition.…”
Section: A Current Carryingmentioning
confidence: 99%